INTRA-OPERATIVE ADMINISTRATION OF AMIODARONE AGAINST POST-OPERATIVE ATRIAL FIBRILLATION IN PATIENTS UNDERGOING ELECTIVE CARDIAC SURGERY - KHAN, AK; PANNU , FY; AMIN , M; IQBAL , S; MUQEET , S (Biological and Clinical Sciences Research Journal, 2024)
Postoperative atrial fibrillation (AF) is a common complication following cardiac surgery, associated with increased morbidity, prolonged hospital stays, and higher healthcare costs. Amiodarone is frequently used as a prophylactic measure to reduce the incidence of AF, but its efficacy and safety in this context remain controversial. Objective: To assess the outcome of peri-operative amiodarone administration for the prevention of atrial fibrillation in patients undergoing elective cardiac surgery. Methods: A prospective study was conducted in the Cardiac Surgery Department of Punjab Institute of Cardiology, Lahore from November 2023 to November 2024. A total of 150 patients undergoing elective cardiac surgery at high risk of developing postoperative atrial fibrillation were selected. The cases group included 75 patients who were administered 400 mg amiodarone twice daily for 5 days before surgery and 5 days after surgery once a day. The control group included 75 patients who were administered placebo treatment. Cardiac surgeries were performed as per usual procedure without any changes. Results: Atrial fibrillation occurred in 30 (40%) patients in the control group and 27 (36%) patients in the cases group, however, this difference was not significant. The mean duration of AF in the control group was 12.5 hours as compared to 15.5 hours in cases, the difference was insignificant. None of the patients died in both groups as reported after 6 weeks follow-up. 6 (8%) patients in the cases group experienced stroke or TIA as compared to none in the control group. 24 (32%) patients in the control group experienced bleeding complications and 3 (4%) patients in the cases groups. Conclusion: No difference in clinical outcomes was observed by administration of amiodarone for prevention of post-op atrial fibrillation.